ANALISIS PERBEDAAN KUALITAS PELAYANAN LEMBAGA KEUANGAN MIKRO KSP. MUGI LESTARI SYARIAH DENGAN BMT MARDHATILLAH BERKAH - Enjang Suherman (BUANA ILMU, 2017)
Abstract The purpose of research analyze the difference of service quality KSP. Mugi Lestari Syariah with BMT Mardhatillah Berkah. The operations of both financial institutions, that the customers to decrease. Beside that, KSP. Mugi Lestari Syariah and BMT Mardhatillah Berkah are members of the Mugi Lestari Group forum. The Mugi Lestari Group has made improvements in the management of its members. Especially KSP. Mugi Lestari Syariah and BMT Mardhatillah Berkah. Handling in improving the quality of service can be done with the same or different depending on the characteristics of both financial institutions. Therefore, Required research to know there is difference or equality in service quality, KSP. Mugi Lestari Syariah with BMT. Mardhatillah Berkah. This research method using comparative study with quantitative descriptive approach verifikatif. This research not only knows the similarity or difference of service quality of both institutions. But can also find out descriptively how the service quality of each financial institution. The results showed that there wasn’t a difference in service quality, KSP. Mugi Lestari Syariah with BMT Mardhatillah Berkah. Using different test Independent Sample T-test found that t arithmetic 0,594